The briefing in paleodesign: selection and arrangement of data for the reconstruction of Paleovertebrates - Ribeiro, Rodolfo Nogueira; Ghilardi, Renato Pirani [UNESP] (My University, 2010)
Representing visually the external appearance of an extinct animal requires, for a reasonably reliable and expressive reconstitution, a good compilation and arrangement of the scientific conclusions on the fossil findings. It is proposed in this work an initial model of a briefing to be applied in a paleodesign process of a paleovertebrate. Briefing can be understood as a gathering of all necessary data to perform a project. We point out what must be known about the relevant structures in order to access all the data and the importance of such information. It is expected that the present briefing suggested might be faced with flexibility, serving as a facilitating interface of the relation between paleoartists and paleontologists.

Representar visualmente a aparência externa de um animal extinto exige uma boa compilação e ordenação das conclusões científicas sobre os achados fósseis, para que esta reconstituição seja razoavelmente informativa e realística, (não esta claro o que o autor quis dizer). Propõe-se aqui um modelo inicial de briefing para ser aplicado num processo de paleodesign de um paleovertebrado. Briefing pode ser entendido como sendo a reunião de todos os dados necessários a execução de um projeto. Explicita-se aqui o que se deve saber sobre as estrutura relevantes, o caminho para se encontrar cada dado e a importância de tal informação. Espera-se que a proposta de briefing seja encarada com flexibilidade e sirva como interface facilitadora da relação entre paleoartistas e paleontólogos.
Keywords: Briefing; Paleodesign; Paleovertebrado; Paleoreconstrução; Paleoreconstruction; Paleovertebrate; Paleodesign; Briefing